Uso de jogos didáticos: o que dizem os professores de Ciências? - SANTOS, Suerley Allana Rosa dos (2024)
Science classes are commonly referred to as content-oriented and expository, with the textbook as the only support material. The didactic game is a pedagogical tool that the teacher can use to make their classes more dynamic and interactive, helping in the teaching and learning process, so that the student can more easily assimilate complex content full of scientific terms. Faced with these prerogatives, the present work aimed to analyze the perceptions of Science teachers about the use of didactic games. This is a qualitative research using a questionnaire with open questions, so that participants could report their past and present experiences regarding the use of didactic games as an educational tool in Science teaching. Five science teachers who work in public basic education in the municipalities of Bragança and Tracuateua, state of Pará, participated in the study. The data obtained were analyzed using interpretive analysis. The results showed that the use of didactic games in Science teaching makes the class more attractive, dynamic and motivating, arousing the student's interest in the content being studied and that the methodology adopted in the classroom influences the student's motivation and learning. Teaching is not an easy task, but with dedication, training and the necessary resources it is possible to make science classes less fragmented, and with greater interaction between students and the content being studied.